THE CONCEPT OF INTELLECTUAL AND SENSUOUS INTUITION: BASIC CONCEPTS AND PROBLEMS - Kyrylenko, Taisa; Lobanovа, Alina (PSYCHOLOGICAL JOURNAL, 2017)
Realizing that the phenomenon of intuition remained in the shadow of philosophy so long and had been one of the mystical and inexplicable, the main task of modern psychology is the study of this phenomenon for its objectification for interaction and practical use. To meet the target set we must focus on understanding the nature of intuition, refer to the mechanisms that are in its basis which is decisive as set vector for further investigations. One of the approaches to the understanding of intuition and opening opportunities for interaction with this phenomenon is to analyze the sensory and rational as two areas that are involved in the process of intuitive knowledge. Since philosophies researchers have been turning to the problem of the origin of knowledge and give the advantage to one of two areas: the sensual (representatives are D. Lokk, E. D. Kondylyak P. Gassendi, Hobbes, L. Feuerbach, A. Brehson) also this idea was developed under the concept of sensationalism; intellectual (representatives are Parmenides, I.G. Fichte, Husserl, Karl Popper) – development of the idea in the concept of rationalism. Particular importance the concept has in M. Bunge researches, where was made the classification of intuition, laying as a basis the ways of intuitive knowledge, as a result distinguishes two kinds of intuition as a characteristics of personality – sensual and intellectual. Sensual intuition by M. Bunge has the following forms: intuition as perception (expressed during the rapid identification of the object, phenomenon or mark a clear understanding of the value or mark, the ability to interpret), intuition as imagination (the ability of the formation of metaphors, imagination). Intellectual intuition M. Bunge classified as follows: intuition as intelligence (accelerated inference), intuition as evaluation (ability to quickly and accurately assess the importance and significance of the problem, the plausibility of the theory). In perspective, considering the phen-omenon of intuition as very difficult to study because of its ambiguous interpretation and hidden mechanisms, this classification is very important and resources for further researches, as its reveals the dynamics of the processes behind the phenomenon. Based on the above considerations, we have developed a questionnaire, which basically comprises two scales: sensuous intuition and intellectual intuition. The questionnaire has been adapted in accordiance with all accepted standards of psychological science. Quite valuable in the development of this tool is that it gives the opportunity to explore the features of intuition in connection with other individual psychological characteristics, which will help to improve knowledge of the phenomenon of intuition’s personality.